2011
DOI: 10.1088/0960-1317/21/10/104014
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic journal bearing with a flexible, damped support operating at 7.2 million DN

Abstract: As the bottleneck for the successful application of ultra-miniature gasturbines is predominantly imposed by limitations in currently available high-speed bearing technology, new bearing concepts have to be developed. This paper reports on the achievement of a record speed of 1 203 000 rpm (= 7.2 million DN) on aerodynamic journal bearings. The concept and implementation of the flexible, damped bearing support are outlined and its effectiveness for the stabilisation of high-speed gas bearings is demonstrated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Stiffness and damping coefficients of the elastic supports which ensure the stability of the rotor are theoretically studied in [8], where it is shown that it is possible to avoid the half-speed whirl. In order to select the support parameters in an optimal way, a stability study is performed in paper [9], in which design guidelines are given.…”
Section: Introductionmentioning
confidence: 99%
“…Stiffness and damping coefficients of the elastic supports which ensure the stability of the rotor are theoretically studied in [8], where it is shown that it is possible to avoid the half-speed whirl. In order to select the support parameters in an optimal way, a stability study is performed in paper [9], in which design guidelines are given.…”
Section: Introductionmentioning
confidence: 99%
“…These results lead to that it is possible to simulate various O-ring support conditions by Eqs. (6,7) within the range of the measurement condition shown in Table 1. Table 3 shows the distribution of the dynamic properties of the O-rings obtained under the measurement conditions shown in Table 1.…”
Section: Identification Of Stiffness and Damping Coefficientsmentioning
confidence: 99%
“…In recent years, this type of bearing systems has attracted considerable attention with a need for increasing rotational speed in small-sized rotational machinery [5][6][7]. Foil bearings have been also investigated as a promising candidate, but their structures and performance are still uncontrolled.…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka et al tested the utilization of these bearings in palmtop gas turbine generators and achieved a rotation of 890,000 rpm using 4 mm diameter journal parts for the shaft for a DN number of 3,560,000 [8,9]. Waumans et al reached 1.2 million rpm (7.2 million DN) using aerodynamic journal bearing with a flexible support [10]. However, aerodynamic bearing needs small radial clearance, the radial clearance of 0.010mm was used.…”
Section: Introductionmentioning
confidence: 99%